Method for manufacturing a composite separator, composite separator, and battery
Patent Information
- Application Number
- CN202611173944.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-09-08
AI Technical Summary
目前常规使用的隔膜(例如聚乙烯隔膜、聚丙烯隔膜)的极性较低、对电解液的浸润性较差,导致离子电导率偏低,且隔膜与电极片的粘附性不足,在电池的充放电循环过程中,隔膜与电极片容易发生界面脱离,容易造成正极片和负极片直接接触引发内部短路的风险
[0035] In one possible implementation of the third aspect, the peel strength between the composite separator and the negative electrode is greater than or equal to 0.26 N/mm. During the battery charge-discharge cycle, this can reduce the risk of the separator separating from the negative electrode and ensure the cycle life of the battery.
Smart Images

Figure CN122716539A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a method for preparing a composite separator, the composite separator, and a battery. Background Technology
[0002] A battery typically consists of electrode plates and a separator. The electrode plates include positive and negative electrodes, and the separator is located between them. Currently used separators (such as polyethylene and polypropylene separators) have low polarity and poor wettability to the electrolyte, resulting in low ionic conductivity. Furthermore, the separator's adhesion to the electrode plates is insufficient. During battery charge-discharge cycles, the separator and electrode plates are prone to interfacial detachment, which can easily lead to direct contact between the positive and negative electrodes and cause an internal short circuit.
[0003] In summary, the diaphragm in related technologies has long suffered from the problem of being unable to simultaneously achieve good adhesion, wettability, and ionic conductivity, thus requiring improvement. Summary of the Invention
[0004] This application provides a method for preparing a composite separator, the composite separator, and a battery. The composite separator prepared by this method has good adhesion, wettability, and high ionic conductivity.
[0005] To achieve the above objectives, the embodiments of this application adopt the following technical solutions: In a first aspect, a method for preparing a composite separator is provided, the method comprising: First, a slurry and a base film are provided. The slurry includes a binder and an organic solvent. The binder is polar, and the base film is a porous polymer base film. When applied in a battery, the porous structure allows metal ions in the electrolyte to freely shuttle between the positive and negative electrodes, forming a current loop. The polarity of the binder significantly increases the concentration of free carriers, contributing to improved ionic conductivity.
[0006] Then, immersing the base membrane in the slurry allows the slurry to fully penetrate the pore structure of the base membrane, resulting in a modified membrane. Subsequently, the modified diaphragm is subjected to freeze treatment, which allows the organic solvents in the slurry to crystallize completely. Finally, the modified membrane after freezing is dried at a temperature below -30°C, which allows the crystalline organic solvent to sublimate directly, resulting in a composite membrane.
[0007] Understandably, traditional room temperature drying and heated drying methods can easily affect the original three-dimensional network framework of the base film, resulting in a reduction in the porosity of the membrane; higher temperatures can also affect the dispersibility of the binder. By subjecting the modified separator to freeze-drying and low-temperature drying, the uniformity of the binder distribution within the base membrane can be ensured, preventing agglomeration or cracking of the binder. Organic solvents can also be removed, preventing them from clogging the surface pores of the base membrane. The binder forms a uniform thin layer in situ on the fiber surface of the base membrane, ensuring the adhesion of the composite separator. Furthermore, the original three-dimensional network framework of the base membrane can be maintained, thus ensuring the porosity of the composite separator and helping to improve the wettability and ionic conductivity of the electrolyte on the surface of the composite separator.
[0008] Because the adhesive has adhesiveness and polarity, and the adhesive is uniformly attached to the outer surface of the base film and the three-dimensional network structure inside the base film, the prepared composite separator can have good adhesion. When the composite separator is applied in the battery, the peel strength between the composite separator and the electrode sheet is large.
[0009] In summary, the composite membrane prepared by the above-described method possesses good adhesion, wettability, and high ionic conductivity. Furthermore, the preparation method is simple and easy to operate.
[0010] In one possible implementation of the first aspect, after immersing the base membrane in the slurry, the preparation method further includes: maintaining the base membrane under a first preset pressure for a first preset time to allow the slurry to penetrate into the pore structure of the base membrane; the first preset pressure is -0.05 MPa to -0.1 MPa, and the first preset time is 1 hour to 2 hours. By completely immersing the base membrane in the slurry and maintaining it under negative pressure for 1 hour to 2 hours, the slurry can fully penetrate into the pore structure of the base membrane.
[0011] In one possible implementation of the first aspect, the temperature for freezing the modified membrane is -50°C to -20°C to ensure that the organic solvent in the modified membrane is completely crystallized.
[0012] In one possible implementation of the first aspect, the modified membrane after freezing is dried in a vacuum environment at a temperature of -50°C to -30°C. On the one hand, this allows the organic solvent ice crystals to sublimate, and the coating on the outer surface of the composite membrane to form a porous structure. On the other hand, the shrinkage rate of the three-dimensional network skeleton of the base membrane is extremely low, allowing the base membrane to maintain its original three-dimensional network structure.
[0013] In one possible implementation of the first aspect, the base film is made of at least one of polyethylene, polypropylene, and polyimide, all of which have a porous structure.
[0014] The base membrane is at least one of non-woven fabric membrane and wet-process membrane, which gives the base membrane a suitable porosity and strong resistance to puncture / dendration.
[0015] In one possible implementation of the first aspect, the porosity of the base membrane is 40% to 60%.
[0016] Understandably, if the porosity of the base membrane is too small, the porosity of the composite membrane will also be too small, leading to obstructed ion transport and affecting the ionic conductivity of the composite membrane. Because the binder has strong polarity, it has better wettability to the electrolyte and a higher liquid absorption rate; therefore, the ionic conductivity of the binder is superior to that of the base membrane. Conversely, if the porosity of the base membrane is too small, the amount of binder entering the three-dimensional network structure of the base membrane will be insufficient, resulting in lower ionic conductivity and inadequate electrolyte wetting of the composite membrane.
[0017] When the porosity of the base membrane is too high, it will significantly weaken the mechanical strength of the separator (especially the puncture resistance). During the battery charge and discharge cycle, the separator is at risk of being punctured by dendrites.
[0018] Therefore, by using a base membrane with a porosity of 40% to 60%, both the composite membrane can be guaranteed to have high ionic conductivity and good electrolyte wettability.
[0019] In one possible implementation of the first aspect, the thickness of the base film is 9 μm to 25 μm.
[0020] Understandably, when a composite separator made from this base film is used in a battery, an excessively thick base film can easily lead to increased internal resistance, decreased energy density, and poor rate performance; while an excessively thin base film can easily result in insufficient mechanical strength and weak puncture / dendrying resistance.
[0021] By using a base film of appropriate thickness, it is possible to reduce the internal resistance of the battery, improve the energy density and rate performance of the battery, and also ensure the mechanical strength of the composite separator and improve its puncture resistance and dendrite resistance.
[0022] In one possible implementation of the first aspect, the adhesive includes at least one of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA). Both PVDF and PMMA are adhesive. Furthermore, the carbon-fluorine bonds in PVDF are strongly polar groups, giving PVDF good wettability to the electrolyte. The methyl groups in PMMA are polar groups, giving PMMA hydrophilicity and good dielectric properties.
[0023] The organic solvents include at least one of acetone, N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. These organic solvents have strong dissolving power, excellent thermal stability, and good chemical compatibility.
[0024] In one possible implementation of the first aspect, the mass fraction of the binder in the slurry is 1 wt% to 10 wt%.
[0025] Understandably, when the binder content in the slurry is too low, the adhesion of the prepared composite membrane is insufficient. When the composite membrane is applied in the battery, the composite membrane and the electrode sheet are prone to interface detachment. When the binder content in the slurry is too high, the binder is prone to clogging the pore structure in the base film, resulting in low ionic conductivity.
[0026] Therefore, by adding 1wt% to 10wt% of binder to the slurry, the adhesion of the prepared composite membrane can be guaranteed, and the possibility of the binder clogging the pore structure in the base membrane can be reduced, thus ensuring the ionic conductivity and electrolyte wetting performance of the composite membrane.
[0027] In one possible implementation of the first aspect, the slurry further includes a plasticizer, wherein the mass ratio of the plasticizer to the binder is 5% to 15%. By adding the aforementioned amount of plasticizer to the slurry, the flexibility of the binder can be improved, the processing fluidity of the slurry can be improved, the glass transition temperature can be lowered, and the impact resistance of the binder in low-temperature environments can be improved.
[0028] In one possible implementation of the first aspect, the slurry further includes a dispersant, wherein the mass ratio of the dispersant to the binder is 1% to 5%. By using a mass ratio of 1% to 5% for the dispersant to the binder in the slurry, the interfacial tension of the binder can be reduced, the organic solvent can be used to quickly wet the surface of the binder, and the binder can be prevented from clumping.
[0029] Secondly, a composite separator is provided, which is prepared by the method described above. It is understood that the beneficial effects achieved by the composite separator of the second aspect provided above can be referenced to the beneficial effects in the first aspect and any possible implementation thereof, and will not be repeated here.
[0030] In one possible implementation of the second aspect, the contact angle of the composite membrane is 22° to 16°. The ionic conductivity of the composite membrane is 1.2 mS / cm to 1.5 mS / cm.
[0031] It should be understood that the smaller the contact angle of the composite separator, the stronger its hydrophilicity, meaning better wettability of the electrolyte on the surface of the composite separator. Applying this composite separator to batteries helps improve the battery's rate performance and cycle life. Furthermore, the high ionic conductivity of this composite separator helps reduce the battery's internal resistance, thereby improving its rate performance and cycle life.
[0032] Thirdly, a battery is provided, which includes a positive electrode, a negative electrode, and a composite separator, wherein the composite separator is the composite separator provided in the second aspect above, and the composite separator is disposed between the positive electrode and the negative electrode.
[0033] Understandably, the beneficial effects that the battery of the third aspect described above can achieve can be referenced to the beneficial effects of the composite separator in the second aspect and any possible implementation thereof, which will not be repeated here.
[0034] In one possible implementation of the third aspect, the peel strength between the composite separator and the positive electrode is greater than or equal to 0.26 N / mm. During the battery charge-discharge cycle, the risk of the separator separating from the positive electrode can be reduced, thus ensuring the cycle life of the battery.
[0035] In one possible implementation of the third aspect, the peel strength between the composite separator and the negative electrode is greater than or equal to 0.26 N / mm. During the battery charge-discharge cycle, this can reduce the risk of the separator separating from the negative electrode and ensure the cycle life of the battery. Attached Figure Description
[0036] Figure 1 This application provides a schematic diagram of the structure of a battery according to some embodiments; Figure 2 for Figure 1 The diagram shows a partial cross-sectional structure of the battery along line AA. Figure 3 This is a schematic diagram of the cross-sectional structure of a composite diaphragm in related technologies; Figure 4 A schematic cross-sectional view of a composite diaphragm provided for some embodiments of this application; Figure 5 Contact angle test diagram of electrolyte on the surface of composite membrane in Example 1, provided in some embodiments of this application; Figure 6 The contact angle test diagram of the electrolyte provided in some embodiments of this application on the surface of the composite membrane of Comparative Example 1 is shown.
[0037] Figure label: 100. Battery; 10. Electrode sheet; 11. Positive electrode sheet; 111. Positive current collector; 112. Positive active layer; 12. Negative electrode sheet; 121. Negative current collector; 122. Negative active layer; 13. Separator; 14. Composite separator; 15. Base membrane; 150. Pore structure; 16. Binder; 160. Coating; 17. Electrolyte. Detailed Implementation
[0038] Hereinafter, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature.
[0039] In embodiments of this application, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.
[0040] In the embodiments of this application, unless otherwise specified, the description of "parallel" indicates approximate parallelism within a certain allowable error range, which can be a range where the angle of deviation from absolute parallelism is less than or equal to 5°. The description of "perpendicular" indicates approximate perpendicularity within a certain allowable error range, which can be a range where the angle of deviation from absolute perpendicularity is less than or equal to 5°.
[0041] In the embodiments of this application, unless otherwise stated, "multiple" means two or more.
[0042] In the embodiments of this application, "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0043] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this application as detailed in the appended claims.
[0044] In some embodiments, see Figure 1 and Figure 2 , Figure 1 This application provides a schematic diagram of the structure of a battery according to some embodiments; Figure 2 for Figure 1The diagram shows a partial cross-sectional view of the battery along line AA. This application provides a battery 100, which can be a single battery cell. The battery 100 includes electrode plates 10 and a separator 13. The electrode plates 10 include a positive electrode plate 11 and a negative electrode plate 12. The positive electrode plate 11 includes a positive current collector 111 and a positive active layer 112 disposed on the surface of the positive current collector 111. The negative electrode plate 12 includes a negative current collector 121 and a negative active layer 122 disposed on the surface of the negative current collector 121. The separator 13 is disposed between the positive electrode plate 11 and the negative electrode plate 12, which can prevent the positive electrode plate 11 and the negative electrode plate 12 from directly contacting each other and causing a short circuit. The separator 13 has a porous structure, which allows metal ions in the electrolyte to freely shuttle between the positive electrode plate 11 and the negative electrode plate 12, forming a current loop.
[0045] The battery 100 can be a sodium-ion battery, a lithium-ion battery, or a magnesium-ion battery, etc., and this application does not limit it.
[0046] Currently, the commonly used separators 13 (such as polyethylene separators and polypropylene separators) have low polarity and poor wettability to electrolytes, resulting in low ionic conductivity of the separators 13. In addition, the adhesion between the separators 13 and the electrode plates 10 is insufficient. During the charge and discharge cycle of the battery 100, the separators 13 are prone to interface detachment from the positive electrode plate 11 and / or the negative electrode plate 12, which may cause the positive electrode plate 11 and the negative electrode plate 12 to come into direct contact and cause the risk of internal short circuit.
[0047] To improve the above-mentioned problems, related technologies often employ coating processes (such as blade coating, spray coating, roller coating, etc.) to form a fluoropolymer coating 160 on the surface of the base film 15, thus creating a composite separator 14. Using this composite separator 14 in the battery 100 can improve the adhesion between the separator 13 and the electrode sheet 10. (Refer to...) Figure 3 , Figure 3 This is a schematic cross-sectional view of the composite membrane 14 in the related technology. The coating 160 obtained by the conventional coating process mainly adheres to the surface of the base membrane 15. While this ensures the adhesion of the composite membrane, it easily clogs some surface pores of the base membrane 15, leading to densification of the coating 160 on the surface of the base membrane 15 and increasing ion transport resistance. Furthermore, during the drying process, due to the capillary contraction force of the liquid phase surface, the coating 160 is prone to agglomeration, cracking, or uneven coverage, resulting in a decrease in the overall porosity of the composite membrane 14, and consequently, impaired electrolyte wettability and ionic conductivity.
[0048] Therefore, the diaphragm 13 and composite diaphragm 14 in the related technologies have long been subject to the technical contradiction of being unable to simultaneously achieve adhesiveness, wettability and ionic conductivity.
[0049] To solve the above-mentioned technical problems, this application provides a method for preparing a composite diaphragm 14, the method comprising: First, a slurry and a base membrane 15 are provided. The slurry includes a binder 16 and an organic solvent. The binder 16 is polar, and the base membrane is a porous polymer base membrane with a three-dimensional network structure. It should be noted that the polarity of the binder 16 means that the binder 16 has polar groups, which generate strong ionic dipole interactions, weaken the Coulomb attraction between anions and cations, significantly increase the concentration of free charge carriers, and help improve ionic conductivity.
[0050] For example, the adhesive 16 includes at least one of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA), that is, the adhesive 16 can be PVDF, PMMA, or a mixture of PVDF and PMMA. The adhesive 16 can be in powder form before being dissolved in an organic solvent.
[0051] Both PVDF and PMMA are adhesive. Furthermore, the carbon-fluorine bond (CF) in PVDF is a strongly polar group, giving PVDF good wettability to electrolytes. The methyl ester group (-COOCH3) in PMMA is a polar group, giving PMMA hydrophilicity and good dielectric properties.
[0052] Then, the base membrane 15 is immersed in the slurry to obtain the modified diaphragm.
[0053] The modified membrane is then subjected to freeze treatment to allow the organic solvents in the slurry to completely crystallize. For example, the impregnated base membrane can be laid flat in a mold or tray and frozen at a low temperature for 12 hours.
[0054] Finally, the modified membrane after freezing is dried at a temperature below -30°C, which allows the crystalline organic solvent to sublimate directly, resulting in a composite membrane.
[0055] See Figure 4 , Figure 4 This is a schematic cross-sectional view of a composite diaphragm 14 provided in some embodiments of this application; by impregnation, the slurry can be fully penetrated into the pore structure 150 of the base membrane 15, so that a portion of the binder 16 in the slurry is uniformly attached to the three-dimensional network structure inside the base membrane 15, and another portion of the binder 16 is distributed on the outer surface of the base membrane 15.
[0056] It is understandable that traditional room temperature drying and heated drying can easily affect the original three-dimensional network skeleton of the base film 15, resulting in a reduction in the porosity of the diaphragm 13; higher temperatures can also affect the dispersibility of the binder 16.
[0057] By subjecting the modified diaphragm 13 to freeze-drying and the aforementioned low-temperature drying process, the uniformity of the adhesive 16 distribution within the base membrane 15 can be ensured, preventing the adhesive 16 from agglomerating or cracking. Furthermore, organic solvents can be removed, preventing them from clogging the surface pores of the base membrane 15. The adhesive 16 forms a uniform thin layer in situ on the fiber surface of the base membrane 15, ensuring the adhesion of the composite diaphragm 14. Additionally, the original three-dimensional network framework of the base membrane 15 can be maintained, thus ensuring the porosity of the composite diaphragm 14, which helps improve the wettability and ionic conductivity of the electrolyte on the surface of the composite diaphragm 14.
[0058] Because the adhesive 16 has adhesiveness and polarity, and the adhesive 16 is uniformly attached to the outer surface of the base film 15 and the three-dimensional network structure inside the base film 15, the prepared composite separator 14 can have good adhesion. When the composite separator 14 is applied in the battery 100, the peel strength between the composite separator 14 and the electrode sheet 10 is large.
[0059] In summary, the composite membrane 14 prepared by the above-described method possesses good adhesion, wettability, and high ionic conductivity. Furthermore, the above preparation method is simple and easy to operate.
[0060] In some embodiments, the organic solvents mentioned above include at least one of acetone, N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide. These organic solvents have strong dissolving power, excellent thermal stability, and good chemical compatibility.
[0061] In some embodiments, the mass fraction of binder 16 in the slurry is 1 wt% to 10 wt%. For example, the mass fraction of binder 16 in the slurry can be 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%.
[0062] Understandably, when the content of binder 16 in the slurry is too low, the adhesion of the prepared composite membrane 14 is insufficient. When the composite membrane 14 is applied in the battery 100, the composite membrane 14 and the electrode sheet 10 are prone to interface detachment. When the content of binder 16 in the slurry is too high, the binder 16 is prone to block the pore structure 150 in the base film 15, resulting in low ionic conductivity.
[0063] Therefore, by adding 1wt% to 10wt% of binder 16 to the slurry, the adhesion of the prepared composite membrane 14 can be guaranteed, and the possibility of binder 16 blocking the pore structure 150 in the base membrane 15 can be reduced, thus ensuring the ionic conductivity and electrolyte wetting performance of the composite membrane 14.
[0064] In some embodiments, the slurry further includes a plasticizer, wherein the mass ratio of the plasticizer to the binder 16 is 5% to 15%. For example, the mass ratio of the plasticizer to the binder 16 in the slurry can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%. The plasticizer can be sodium carboxymethyl cellulose (CMC).
[0065] By adding the plasticizer of the above content to the slurry, the flexibility of the binder 16 can be improved, the processing fluidity of the slurry can be improved, the glass transition temperature can be reduced, and the impact resistance of the binder 16 in low-temperature environments can be improved.
[0066] In some embodiments, the slurry further includes a dispersant, wherein the mass ratio of the dispersant to the binder 16 is 1% to 5%. For example, the mass ratio of the dispersant to the binder 16 in the slurry can be 1%, 2%, 3%, 4%, or 5%. The dispersant can be polyvinylpyrrolidone (PVP).
[0067] By using a mass ratio of dispersant to binder 16 of 1% to 5% in the slurry, the interfacial tension of binder 16 can be reduced, the organic solvent can be used to quickly wet the surface of binder 16, and the caking of binder 16 can be avoided.
[0068] For example, the preparation method of the above slurry includes: mixing the above binder 16, organic solvent, plasticizer and dispersant, stirring for 6 hours at 40°C to 60°C (e.g. 40°C, 50°C or 60°C) until completely dissolved, and then allowing it to stand to degas.
[0069] In some embodiments, after immersing the base membrane 15 in the slurry, the preparation method further includes: maintaining the base membrane 15 under a first preset pressure for a first preset time to allow the slurry to penetrate into the pore structure 150 of the base membrane 15; the first preset pressure is -0.05 MPa to -0.1 MPa, and the first preset time is 1 hour to 2 hours. For example, the first preset pressure can be -0.05 MPa, -0.06 MPa, -0.07 MPa, -0.08 MPa, -0.09 MPa, or -0.1 MPa. The first preset time can be 1 hour, 1.5 hours, or 2 hours.
[0070] By immersing the base membrane 15 completely in the above slurry and maintaining it under negative pressure for 1 to 2 hours, the slurry can fully penetrate into the pore structure 150 of the base membrane 15.
[0071] Of course, in some other embodiments, the base membrane 15 can also be immersed in the slurry under normal pressure. Alternatively, the base membrane 15 can be immersed in the slurry under normal pressure for 1 to 2 hours, and then kept in the slurry under the above-mentioned negative pressure for 1 to 2 hours, so that the slurry can fully penetrate into all the pores of the base membrane 15.
[0072] In some embodiments, the modified membrane 13 is frozen at a temperature of -50°C to -20°C to ensure complete crystallization of the organic solvent in the modified membrane 13. For example, the freezing temperature can be -50°C, -40°C, -30°C, or -20°C. The frozen modified membrane 13 is then dried in a vacuum environment to allow the organic solvent ice crystals to sublimate directly until the weight of the modified membrane 13 no longer changes. The drying temperature of -50°C to -30°C ensures both the direct sublimation of the organic solvent ice crystals and the preservation of the original three-dimensional network structure of the base membrane 15. For example, the drying temperature can be -50°C, -40°C, or -30°C, and the drying time can be 48 hours.
[0073] For example, the modified diaphragm 13 after freezing can be placed in a freeze dryer, which is a vacuum environment with a vacuum degree less than or equal to 10 Pa. It should be noted that the vacuum degree refers to the degree of rarefaction of the gas, and is numerically equal to atmospheric pressure minus absolute pressure.
[0074] Drying in a low-temperature vacuum environment allows organic solvent ice crystals to sublimate, resulting in a porous and loose structure in the coating of the composite membrane 14. The shrinkage rate of the three-dimensional network skeleton of the base membrane 15 is extremely low, allowing the base membrane 15 to maintain its original three-dimensional network structure.
[0075] In some embodiments, the base membrane 15 is made of at least one of polyethylene (PE), polypropylene (PP), and polyimide (PI); the base membrane 15 is at least one of a nonwoven membrane 13 and a wet-laid membrane 13. All of the above-mentioned base membranes 15 have a porous structure 150, and the porosity of the base membrane 15 is 40% to 60%. For example, the porosity of the base membrane 15 can be 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, or 60%. The porosity of the base membrane 15 refers to the ratio of the volume of micropores in the base membrane 15 to the total volume of the membrane 13.
[0076] Understandably, when the porosity of the base membrane 15 is too small (less than 40%), the porosity of the composite membrane 14 will also be too small, leading to obstructed ion transport and affecting the ionic conductivity of the composite membrane 14. Because the binder 16 has strong polarity, it has better wettability to the electrolyte and a higher liquid absorption rate; therefore, the ionic conductivity of the binder 16 is superior to that of the base membrane 15. Conversely, when the porosity of the base membrane 15 is too small, the amount of binder 16 entering the three-dimensional network structure of the base membrane 15 is insufficient, resulting in lower ionic conductivity and inadequate electrolyte wetting of the composite membrane 14.
[0077] When the porosity of the base film 15 is too high (greater than 60%), it will significantly weaken the mechanical strength of the separator 13 (especially the puncture resistance). During the charge and discharge cycle of the battery 100, the separator 13 is at risk of being punctured by dendrites.
[0078] Therefore, by using a base membrane 15 with a porosity of 40% to 60%, both the composite membrane 14 can be guaranteed to have high ionic conductivity and electrolyte wettability.
[0079] In some embodiments, the thickness of the base film 15 is 9 μm to 25 μm. For example, the thickness of the base film 15 can be 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm or 25 μm.
[0080] It is understandable that when the composite separator 14 made from the base film 15 is applied to the battery 100, if the thickness of the base film 15 is too large, it will easily lead to an increase in the internal resistance of the battery 100, a decrease in the energy density of the battery 100, and a deterioration in the rate performance; if the thickness of the base film 15 is too small, it will easily lead to insufficient mechanical strength and weak puncture resistance / dendrying resistance.
[0081] By using a base film 15 of appropriate thickness, it is possible to reduce the internal resistance of the battery 100, improve the energy density and rate performance of the battery 100, and also ensure the mechanical strength of the composite separator 14, thereby improving its puncture resistance and dendrite resistance.
[0082] In some embodiments, this application also provides a composite diaphragm 14, which is prepared by the preparation method of the composite diaphragm 14 of any of the above embodiments.
[0083] Understandably, the beneficial effects that the composite membrane 14 can achieve can be referred to the beneficial effects of the preparation method of the composite membrane 14 described above, and will not be repeated here.
[0084] In some embodiments, the contact angle of the composite membrane 14 is 22° to 16°; the ionic conductivity of the composite membrane 14 is 1.2 mS / cm to 1.5 mS / cm. For example, the contact angle of the composite membrane 14 can be 22°, 21.5°, 21°, 20.6°, 20.5°, 20.3°, 20°, 19°, 18.5°, 18°, 17°, or 16°; the ionic conductivity of the composite membrane 14 can be 1.2 mS / cm, 1.25 mS / cm, 1.27 mS / cm, 1.3 mS / cm, 1.4 mS / cm, or 1.5 mS / cm.
[0085] It should be understood that the smaller the contact angle of the composite separator 14, the stronger its hydrophilicity, meaning better wettability of the electrolyte on the surface of the composite separator 14. When this composite separator 14 is applied to the battery 100, it helps to improve the rate performance and cycle life of the battery 100. Furthermore, because the composite separator 14 has high ionic conductivity, its application to the battery 100 helps to reduce the internal resistance of the battery 100, thereby improving its rate performance and cycle life.
[0086] In some embodiments, this application also provides a battery 100, which includes a positive electrode 11, a negative electrode 12, and the aforementioned composite separator 14, wherein the composite separator 14 is disposed between the positive electrode 11 and the negative electrode 12. It is understood that the beneficial effects achievable by this battery 100 can be referenced to the beneficial effects of the aforementioned composite separator 14, and will not be repeated here.
[0087] This application also provides a method for preparing a battery 100, the method comprising: first, providing a positive electrode shell, a negative electrode shell, a gasket, a spring sheet, a positive electrode plate 11, a negative electrode plate 12, a composite separator 14, and an electrolyte, wherein the composite separator 14 is the composite separator 14 of the above embodiments of this application. Then, assembling a simulated battery 100 in a glove box with a dew point below -40°C, sequentially stacking the positive electrode shell, the positive electrode plate 11, and the composite separator 14, and adding 80μL~100μL of electrolyte to the composite separator 14 to ensure that the electrolyte completely wets the separator 13; next, sequentially stacking the negative electrode plate 12, the gasket, the spring sheet, and the negative electrode shell on the separator 13, and pressing them together with a sealing machine. Finally, allowing the assembled battery 100 to stand at room temperature for 2 hours to allow the electrolyte to fully wet the separator 13.
[0088] In some embodiments, the peel strength between the composite separator 14 and the positive electrode 11 is greater than or equal to 0.26 N / mm. During the charge-discharge cycle of the battery 100, this reduces the risk of the separator 13 detaching from the positive electrode 11, thus ensuring the cycle life of the battery 100. For example, the peel strength between the composite separator 14 and the positive electrode 11 can be 0.26 N / mm, 0.27 N / mm, 0.28 N / mm, 0.29 N / mm, 0.3 N / mm, 0.32 N / mm, 0.35 N / mm, or 0.4 N / mm.
[0089] The peel strength between the composite separator 14 and the negative electrode 12 is greater than or equal to 0.26 N / mm. During the charge-discharge cycle of the battery 100, this can reduce the risk of the separator 13 detaching from the negative electrode 12 and ensure the cycle life of the battery 100. For example, the peel strength between the composite separator 14 and the negative electrode 11 can be 0.26 N / mm, 0.27 N / mm, 0.28 N / mm, 0.29 N / mm, 0.3 N / mm, 0.32 N / mm, 0.35 N / mm, or 0.4 N / mm.
[0090] Contact angle tests can be performed on the composite diaphragm 14 of this application embodiment and the composite diaphragm 14 in related technologies to verify that the composite diaphragm 14 of this application embodiment has good wettability. Therefore, two preparation methods are set up: Example 1 and Comparative Example 1. The composite diaphragm 14 of this application embodiment is prepared by Example 1, and the composite diaphragm 14 in related technologies is prepared by Example 2.
[0091] Example 1 is as follows: First, weigh 10g of PVDF powder and dissolve it completely in 490g of NMP. Add 0.5g of PVP as a dispersant and 0.5g of CMC as a plasticizer to the mixture of PVDF and NMP, stir at 50°C for 6 hours until completely dissolved, and let stand for 2 hours to remove bubbles.
[0092] Then, a PE wet-process separator 13 with a thickness of 16 μm and a porosity of 55% is cut into 15 cm × 20 cm pieces to form a base membrane 15. The base membrane 15 is completely immersed in the PVDF-containing slurry and soaked for 60 minutes under normal pressure, with slight shaking during the soaking to ensure full wetting of the base membrane 15. The base membrane 15 is then completely immersed in the PVDF slurry and kept under negative pressure (e.g., -0.05 to -0.09 MPa) for 60 minutes to allow the slurry to fully penetrate into the pore structure 150 of the base membrane 15, thus obtaining the modified separator 13.
[0093] Afterwards, take out the modified diaphragm 13, lay it flat on a stainless steel tray, and freeze it in a -25°C freezer for 12 hours.
[0094] Finally, the frozen modified diaphragm 13 was quickly transferred to a freeze dryer, the cold trap temperature was set to -45°C, the vacuum degree was 5Pa, and it was dried for 48 hours to obtain the composite diaphragm 14.
[0095] Comparative Example 1 is as follows: Using the same base membrane 15 as in Example 1, 5wt% PVDF slurry was sprayed onto the surface of the separator 13, with a coating thickness of 3μm. After drying in a forced-air environment at 60℃ for 12 hours, a conventional coated composite separator 14 was obtained.
[0096] The contact angle test procedure is illustrated below: First, the composite membrane 14 samples obtained in Example 1 and Comparative Example 1 were smoothly adhered to the stage using double-sided tape, ensuring no air bubbles or warping. Then, the electrolyte was injected into a microsyringe to expel air bubbles. Measurement parameters were set as follows: droplet volume 3 μL, droplet rate 1 μL / s, recording frequency 30 frames / second; ambient temperature controlled at 25±1℃, relative humidity <10%. Next, electrolyte droplets were automatically dropped onto the surfaces of the two different composite membrane 14 samples and allowed to stand for 1 second to stabilize. Finally, the angle between the electrolyte droplet and the surface of the composite membrane 14 was recorded using a contact angle meter; this angle is the contact angle. The contact angle measurement data are shown in Table 1.
[0097] The peel strength test procedure between the composite separator 14 and the electrode sheet 10 is illustrated below: The electrode sheet 10 (e.g., a negative electrode sheet 12 or a positive electrode sheet 11) is placed flat on the worktable with the coated surface facing upwards. The composite separator 14 sample is aligned and placed over the coated surface of the electrode sheet 10, then placed on a hot press. The hot pressing parameters (simulating actual battery processes) are set as follows: temperature 80±2℃, pressure 1MPa, time 5min. After hot pressing, the composite separator 14 and electrode sheet 10 are removed as a whole and allowed to stand at room temperature for 30min. The composite separator 14 and electrode sheet 10 are then cut into pieces 20mm wide. The electrode sheet 10 is fixed to the lower clamp of the tensile testing machine, and the free end of the composite separator 14 is clamped to the upper clamp, ensuring a peel angle of 180°.
[0098] The composite membranes 14 obtained in Example 1 and Comparative Example 1 can be tested according to the above peel strength test process, and the test results are shown in Table 1.
[0099] An example of the experimental procedure for testing the ionic conductivity of the composite separator 14 is as follows: The composite separator 14 of Example 1 can be applied to a battery to obtain a first battery, which can be prepared according to the preparation method of battery 100 described above; the composite separator 14 of Comparative Example 1 can be applied to a battery to obtain a second battery, which can also be prepared according to the preparation method of battery 100 described above. Electrochemical tests are then performed on the first battery and the second battery respectively to verify the ionic conductivity of the composite separator 14 of this application embodiment.
[0100] Both the first and second batteries were connected to an electrochemical workstation in a two-electrode configuration, with the working electrode and reference / counter electrode connected to the two electrode plates 10 of battery 100, respectively. AC impedance testing parameters were set as follows: frequency range 0.1 Hz to 1 MHz, amplitude 5 mV. The obtained ionic conductivity data are shown in Table 1.
[0101] Table 1 Performance test results of composite membrane
[0102] See Figure 5 , Figure 6 And in conjunction with Table 1, Figure 5 Contact angle test diagram of electrolyte 17 on the surface of composite membrane 14 in Example 1, provided for some embodiments of this application; Figure 6 The diagram shows the contact angle test results of electrolyte 17 on the surface of composite membrane 14 in Comparative Example 1, provided in some embodiments of this application. The contact angle α of electrolyte 17 on the surface of composite membrane 14 in Example 1 is 20.6°, and the contact angle β of electrolyte 17 on the surface of composite membrane 14 in Comparative Example 1 is 30.9°. This indicates that the composite membrane 14 prepared according to the preparation method of the embodiments of this application has better hydrophilicity and excellent wettability of electrolyte 17.
[0103] As shown in Table 1, the ionic conductivity of the composite separator 14 in Example 1 (1.27 mS / cm) is 25.7% higher than that of the composite separator 14 in Comparative Example 1 (1.01 mS / cm). This indicates that the composite separator 14 prepared according to the preparation method of this application has higher ionic conductivity. When the composite separator 14 is applied to a battery, it helps to reduce the internal resistance of the battery 100, thereby improving the rate performance of the battery 100 and improving the cycle life of the battery 100.
[0104] Furthermore, the peel strength between the composite diaphragm 14 and the electrode sheet 10 in Example 1 is only slightly different from that in Comparative Example 1. This demonstrates that the composite diaphragm 14 in Example 1 maintains a certain level of adhesion while significantly improving wettability and ionic conductivity.
[0105] The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. The above embodiments only illustrate several implementation methods of this application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of this application. It should be noted that for those skilled in the art, several modifications and improvements can be made without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.
[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing a composite diaphragm, characterized in that, include: A slurry and a base film are provided, the slurry comprising a binder and an organic solvent, the binder being polar, and the base film being a porous polymer base film; The base membrane is immersed in the slurry to obtain a modified diaphragm; The modified diaphragm is subjected to a freeze treatment; The modified diaphragm after freezing was dried at a temperature below -30°C to obtain a composite diaphragm.
2. The preparation method according to claim 1, characterized in that, After immersing the base membrane in the slurry, the preparation method further includes: maintaining the base membrane under a first preset pressure for a first preset time to allow the slurry to penetrate into the pore structure of the base membrane; the first preset pressure is -0.05MPa to -0.1MPa, and the first preset time is 1 hour to 2 hours.
3. The preparation method according to claim 1, characterized in that, The modified diaphragm is subjected to freezing treatment at a temperature of -50℃ to -20℃; and / or, the frozen modified diaphragm is subjected to drying treatment in a vacuum environment at a temperature of -50℃ to -30℃.
4. The preparation method according to claim 1, characterized in that, The base film satisfies at least one of the following conditions: (1) The base film is made of at least one of polyethylene, polypropylene, and polyimide; (2) The base membrane is at least one of non-woven fabric diaphragm and wet-process diaphragm; (3) The porosity of the base membrane is 40%~60%; (4) The thickness of the base film is 9μm~25μm.
5. The preparation method according to claim 1, characterized in that, The adhesive comprises at least one of polyvinylidene fluoride and polymethyl methacrylate; and / or, the organic solvent comprises at least one of acetone, N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.
6. The preparation method according to claim 1, characterized in that, The slurry satisfies at least one of the following conditions: (1) The mass fraction of the binder in the slurry is 1wt%~10wt%; (2) The slurry further includes a plasticizer, wherein the mass ratio of the plasticizer to the binder is 5% to 15%; (3) The slurry also includes a dispersant, wherein the mass ratio of the dispersant to the binder is 1% to 5%.
7. A composite diaphragm, characterized in that, include: It is prepared by the method of preparing the composite diaphragm according to any one of claims 1-6.
8. The composite diaphragm according to claim 7, characterized in that, The contact angle of the composite membrane is 22°~16°; and / or the ionic conductivity of the composite membrane is 1.2mS / cm~1.5mS / cm.
9. A battery, characterized in that, include: Positive and negative electrode plates; The composite separator is the composite separator as described in claim 7 or 8, wherein the composite separator is disposed between the positive electrode and the negative electrode.
10. The battery according to claim 9, characterized in that, The peel strength between the composite separator and the positive electrode is greater than or equal to 0.26 N / mm.